Website for hospitals technological management system support (2004)
A Web site is presented by this document, where users will be able to find a guide to implement the technological management at hospitals and to download the informatics system for maintenance management (SMACOR). This work will fill the emptiness in technological management matter that exists today in Cuban and Latin America Healthcare networks. This product is the result of a more than a decade long researching work at this branch done by the Bioengineering Center (CEBIO) at the ISPJAE University in Havana City.